Sustainability Transition in Tunisian Companies: Challenges, Dynamics, and Comparative Perspectives - FARHOUD, Mohamed (Journal of Environmental Management and Tourism; Vol 16 No 4 (2025): JEMT, Volume XVI, Issue 4(80), Winter 2025DO - 10.14505/jemt.v16.4(80).02, 2025)
This article explores the sustainability transition of Tunisian companies in a context characterized by institutional instability, limited access to green financing, and weak regulatory incentives. Using a mixed-methods approach, the study combines a quantitative survey of 120 companies, 20 semi-structured interviews with key stakeholders, an international comparative analysis (France, Germany, Morocco), and a broader regional perspective encompassing MENA countries (Middle East and North Africa). Results show growing awareness of sustainability, but implementation remains limited. The study identifies internal/external barriers and highlights levers to overcome them. The integration of the MENA regional perspective enriches the analysis by situating the findings within a broader framework, revealing both convergences and specificities. The article offers concrete recommendations for policymakers, entrepreneurs, and researchers, emphasizing the need for systemic change involving managerial innovation, policy reforms, and greater stakeholder engagement.